Identification of Institutional Barriers to Regional Entrepreneurship Development (A Critical Approach to Historical System of Entrepreneurship Development Policy Making) - Bahman Khodapanah; Mohammad Ali Moradi; Hamid Padash; Kamal Sakhdari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Entrepreneurship transforms the challenges of regions into opportunities such as increasing employment and income rates, reducing crimes caused by unemployment and poverty. Clearly, entrepreneurship development is not possible without efficient institutions that respond creatively and entrepreneurially to local and regional issues and challenges. Hence, the purpose of the present study is to identify the institutional barriers to entrepreneurship development in Iran from a historical perspective before the Islamic Revolution of 1979. Therefore, 12 sources related to Iran's underdevelopment have been selected and were analyzed by using the theme analysis strategy and Atlas T software in two stages of open and axial coding. According to the results, the main root of entrepreneurship underdevelopment in Iran should be examined in the course of history, and the unfavorable business environment at the present time is not the only reason for the lack of entrepreneurship development in Iran . The most important institutional barriers identified in the studied texts can be classified into 6 main categories: administrative barriers, economic barriers, social and cultural barriers, legal and regulatory barriers, political barriers, personal and cognitive barriers, which are part of these barriers (administrative, economic, legal-regulatory, political) in the category of formal institutions and another part (socio-cultural and cognitive-personal) in the category of informal institutions.